A product and a formula

Calculus Level 5

What is the value of a > 0 a > 0 such that

3 π = n = 1 ( 1 a 2 n 2 π 2 ) ? \large \frac{3}{\pi} = \prod_{n = 1}^{\infty} \left ( 1 - \frac{a^2}{n^2 \pi^2} \right)?


The answer is 0.52359.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Using the following identity ( equation 23 ),

sin x x = n = 1 ( 1 x 2 n 2 π 2 ) 3 π = n = 1 ( 1 a 2 n 2 π 2 ) sin a a = 3 π a = π 6 0.524 \begin{aligned} \frac {\sin x}x & = \prod_{n=1}^\infty \left(1-\frac {x^2}{n^2\pi^2}\right) \\ \frac 3\pi & = \prod_{n=1}^\infty \left(1-\frac {a^2}{n^2\pi^2}\right) \\ \implies \frac {\sin a}a & = \frac 3\pi \\ \implies a & = \frac \pi 6 \approx \boxed{0.524} \end{aligned}

If 0 < t < π 0 < t < \pi , then cot ( t ) = 1 t + n = 1 2 t t 2 n 2 π 2 \displaystyle \cot (t) = \frac{1}{t} + \sum_{n = 1}^{\infty} \frac{2t}{t^2 - n^2 \cdot \pi^2} . Then, if 0 < α < x < π 0 < \alpha < x < \pi , log sin ( x ) x log sin ( α ) α = α x ( cos ( t ) sin ( t ) 1 t ) d t = α x n = 1 2 t t 2 n 2 π 2 = \displaystyle \log \frac{\sin (x)}{x} - \log \frac{\sin (\alpha)}{\alpha} = \int_{\alpha}^x (\frac{\cos (t)}{\sin (t)} - \frac{1}{t}) \, dt = \int_{\alpha}^x \sum_{n = 1}^{\infty} \frac{2t}{t^2 - n^2 \cdot \pi^2} = = n = 1 log ( x 2 n 2 π 2 α 2 n 2 π 2 ) = \displaystyle \sum_{n = 1}^{\infty} \log \left ( \frac{x^2 - n^2 \cdot \pi^2 }{\alpha^2 - n^2 \cdot \pi^2} \right ) \Rightarrow as α 0 , log sin ( x ) x = n = 1 log ( x 2 n 2 π 2 n 2 π 2 ) sin ( x ) x = n = 1 ( 1 x 2 n 2 π 2 ) \alpha \rightarrow 0, \log \frac{\sin (x)}{x} = \sum_{n = 1}^{\infty} \log \left ( \frac{x^2 - n^2 \cdot \pi^2 }{ - n^2 \cdot \pi^2} \right ) \Rightarrow \frac{\sin (x)}{x} = \prod_{n = 1}^\infty \left ( 1 - \frac{x^2}{n^2 \pi^2} \right ) \Rightarrow 3 π = 1 2 π 6 = sin ( π 6 ) π 6 = n = 1 ( 1 a 2 n 2 π 2 ) a = π 6 \frac{3}{\pi} = \frac{ \frac{1}{2}}{\frac{\pi}{6}} = \frac{\sin (\frac{\pi}{6})}{\frac{\pi}{6}} = \prod_{n = 1}^\infty \left ( 1 - \frac{a^2}{n^2 \pi^2} \right ) \Rightarrow a = \frac{\pi}{6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...